Lung resided monocytic myeloid-derived suppressor cells contribute to premetastatic niche formation by enhancing MMP-9 expression. (April 2020) - Zhang, Juechao; Han, Xiaoqing; Shi, Huifang; Gao, Yanyan; Qiao, Xuan; Li, Huihan; Wei, Min; Zeng, Xianlu
Abstract: In cancer patients, the prevalence of myeloid-derived suppressor cells (MDSCs) is correlated with the degree of malignancy. In the present study, we investigated the role of circulating M-MDSCs in premetastatic niche formation using a mouse syngeneic tumor model and found that there was an increased frequency of M-MDSCs in the peripheral blood of tumor-bearing mice. M-MDSCs tracking and lung tissue histological analyses revealed that the malignant conditions promote the residence of circulating M-MDSCs and increased tumor cell arrest in the lungs. We further found that MMP-9 expression was increased in the circulating M-MDSCs and the administration of an MMP-9 inhibitor suppressed M-MDSCs transplantation-induced tumor cell arrest in the lung. Therefore, our findings suggest that the expansion of circulating M-MDSCs during tumor progression contributes to premetastatic niche formation by increasing MMP-9 expression. Highlights: M-MDSC depletion reduced tumor cell arrest in the lungs. MMP-9 expression was increased among circulating M-MDSCs. M-MDSCs contribute to premetastatic niche formation by increasing MMP-9 expression.